2015
DOI: 10.1136/jnnp-2014-310055
|View full text |Cite
|
Sign up to set email alerts
|

Identifying who will benefit from non-invasive ventilation in amyotrophic lateral sclerosis/motor neurone disease in a clinical cohort

Abstract: Between 1991 and 2011, 1198 patients diagnosed with ALS/MND were registered. 929 patients (77.5%) fulfilled the selection criteria and their data were analysed. Median tracheostomy free survival from symptom onset was 28 months in NIV-treated patients compared to 15 months in untreated (Univariate Cox regression HR=0.61 (0.51 to 0.73), p<0.001). The positive survival effect of NIV persisted when the model was adjusted for age, gender, riluzole and percutaneous endoscopic gastrostomy use (HR=0.72 (0.60 to 0.88,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 31 publications
7
93
2
5
Order By: Relevance
“…Similar to other studies that showed that only [23] 6% to 30% of ALS patients use NIV [30,31], the frequency of NIV use was low in the present study (18%), which is related to economic factors and to the long delay in diagnostic time. However, strong evidence exists that shows that NIV prolongs survival in ALS patients [4,30,32].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar to other studies that showed that only [23] 6% to 30% of ALS patients use NIV [30,31], the frequency of NIV use was low in the present study (18%), which is related to economic factors and to the long delay in diagnostic time. However, strong evidence exists that shows that NIV prolongs survival in ALS patients [4,30,32].…”
Section: Discussionsupporting
confidence: 74%
“…However, strong evidence exists that shows that NIV prolongs survival in ALS patients [4,30,32]. In a recent study [30], the median tracheostomy-free survival from symptom onset was 28 months in NIV-treated patients, compared to 15 months for untreated patients, and the benefit persisted after adjusting for age, gender, riluzole use and gastrostomy use. However, the only randomized controlled trial of NIV did not support this finding [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors, such as site of disease onset (bulbar versus limb), have a more complex effect on survival that is influenced by age and gender (13,14). Survival can be prolonged through initiation of non-invasive ventilation (NIV) (15), which is sometimes considered as a secondary endpoint for disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Edavarone has also been found to be beneficial [10] . Noninvasive ventilation (NIV) is available when the disease involves their respiratory system and can prolong the survival of the patients [11] . In the last decades, some drugs shown encouraging results on the rodent ALS models, but have proved to be ineffective in clinical trials of ALS patients [12] .…”
Section: Table 1 El Escorial Criteria For Alsmentioning
confidence: 99%